2020
DOI: 10.1016/j.cgh.2019.12.029
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Microbiota Transplant Decreases Mortality in Patients with Refractory Severe or Fulminant Clostridioides difficile Infection

Abstract: BACKGROUND & AIMS:Fecal microbiota transplantation (FMT) is recommended for recurrent Clostridioides difficile infection (CDI). FMT cures nearly 80% of patients with severe or fulminant CDI (SFCDI) when utilized in a sequential manner. We compared outcomes of hospitalized patients before and after implementation of an FMT program for SFCDI and investigated whether the changes could be directly attributed to the FMT program. METHODS:We performed a retrospective analysis of characteristics and outcomes of patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 39 publications
2
47
0
Order By: Relevance
“…A balance of risks and benefits should guide a joint decision of either FMT or (tapered) antibiotics with or without additional treatment with, for example, monoclonal antibody or nonabsorbable antibiotics. Few studies have addressed the effects of FMT in patients with refractory or severe CDI, although FMT as rescue treatment appears encouraging 40,63,83–86 . We suggest FMT as an option for patients with refractory or severe CDI.…”
Section: Clinical Application Of Fmtmentioning
confidence: 91%
See 1 more Smart Citation
“…A balance of risks and benefits should guide a joint decision of either FMT or (tapered) antibiotics with or without additional treatment with, for example, monoclonal antibody or nonabsorbable antibiotics. Few studies have addressed the effects of FMT in patients with refractory or severe CDI, although FMT as rescue treatment appears encouraging 40,63,83–86 . We suggest FMT as an option for patients with refractory or severe CDI.…”
Section: Clinical Application Of Fmtmentioning
confidence: 91%
“…Few studies have addressed the effects of FMT in patients with refractory or severe CDI, although FMT as rescue treatment appears encouraging. 38,63,[83][84][85][86] We suggest FMT as an option for patients with refractory or severe CDI. The route of FMT application in severely ill patients should be guided by the complication risk of the individual patient.…”
Section: Indications and Contraindications For Fmtmentioning
confidence: 99%
“…effectiveness of the different strategies although the importance of previous severity in recurrences and its impact on the effectiveness of treatment is not known. Additionally, CDI related morality was similar amongst all treatment options despite the recent studies showing that mortality rates with FMT are relatively lower than antibiotic treatment [34,35]. The results of the sensitivity analysis have shown that this assumption has minimal effect on the base case result.…”
Section: Discussionmentioning
confidence: 85%
“…Different scenarios were explored to include (i) the response to treatment and recurrence rates for FMT colonoscopy and NGT were a assumed to be the same, (ii) length of hospital stay for FMT options were changed from 5 to 10 days (iii) similar recurrence rates for all treatment options (iv) constant efficacy for the first and second dose of FMT (v) the cost of all treatment options was varied using the parameter range presented in Table 1. Further sensitivity analysis was carried out to explore other potential assumption relating to the lower CDI related mortality associated with FMT [34,35].…”
Section: Model Analysismentioning
confidence: 99%
“…For refractory CDI, even though exclusion of other causes is required (for example ulcerative colitis, microscopic colitis), FMT as rescue treatment appears encouraging, although few studies have addressed the effects of FMT in patients with refractory or severe CDI [32][33][34][35][36][37]. Furthermore, FMT appeared to decrease mortality in patients with severe CDI refractory to antibiotic therapy [34][35][36]38], and could also be considered as a therapeutic option for this condition, with decision taken on a case-by-case basis.…”
Section: Which Patients With CDI Should Be Considered For Fmt?mentioning
confidence: 99%